Pengaruh Investment Opportunity Set Dan Kepemilikan Manajerial Terhadap Nilai Perusahaan Dengan Kebijakan Hutang Sebagai Variabel Intervening - Sheyla Salima Oktabrina; Komala Inggarwati (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aims to determine the effect of Investment Opportunity Set and Managerial Ownership to Firm Value through Debt Policy as Intervening Variable at Manufacture Company. The sample in this study were 27 companies from sub-sector Industrials. Stages of testing include outer model, reliability and consistency, convergent and discriminant validity, inner model, coefficient determinations, effect size, prediction relevance, and path coefficient. The analysis used in this research is SEM-PLS. The result showed that; (1) Investment opportunity set positively influences firm value, (2) Managerial ownership has no effect on firm value, (3) Investment opportunity set negatively influences debt policy, (4) Managerial ownership has no effect on debt policy, (5) Debt policy positively influences firm value (6) Investment opportunity set negatively influences firm value with debt policy as intervening variable, (7) Managerial ownership has no effect on firm value with debt policy as intervening variable. Keywords: Investment opportunity set, managerial ownership, firm value, debt policy